OBSERVATIONS ON THE SECONDARY SEXUAL CHARACTERS OF HIPPOLYSMATA ENSIROSTRIS KEMP - Sukumaran, K K (Indian Journal of Fisheries, 2011)
Hermaphrodites are seldom found among prawns. In Hippotysmata ensirostrisKemp, a commercially important shrimp of Maharashtra belonging to the familyHippolytidae hermaphroditism has been observed as a regular feature and this is thefirst record of its kind in this species. The prawn matures as male in the early partof it; life and later, changes its sex completely and functions as female during the remainingperiod. Subsequent changes in the secondary sex characters have been noticedin the sex change